DIGITAL TRANSFORMATION OF THE HEALTHCARE SYSTEM: NEW APPROACHES TO TRAINING REHABILITATION PROFESSIONALS - Рисована, Любов; Радзішевська, Євгенія; Григорук, Вікторія; Алексеєнко, Роман (SWorldJournal, 2025)
This article examines current trends in the training of prosthetics and orthotics specialists within the context of the ongoing digital transformation of medical rehabilitation. The study highlights key directions in the development of the field, with pa